THE IMPLEMENTATION OF TUTORIAL VIDEO TO IMPROVE STUDENTSâ€™ SKILL IN WRITING PROCEDURE TEXT - Ratri Ikadestanti; Nanik Supriani (JELLT (Journal of English Language and Language Teaching), 2017)
The objectives of this study are to describe the studentsâ€™ writing skills taught using tutorial video in writing a procedure text, to describe the studentsâ€™ writing skills taught using conventional method in writing procedure text, Â to find out the difference between studentsâ€™ who were taught using tutorial video and conventional method in writing procedure text, and to find out whether or not the class which is taught using tutorial video is better than the class using conventional method. This research was experimental research. The participants were the second grade students of SMK N 5 Yogyakarta. The results showed that the level of studentsâ€™ writing skills taught using tutorial video was categorized as â€œvery highâ€ at the category scale 75-above (Mean= 80.11 and SD= 6.716), the level of studentsâ€™ writing skills taught using conventional method categorized as â€œhighâ€ at the category scale 58.33-75 (Mean = 63.64 and SD= 6.302), the result of t-test showed Sig. (2-tailed) level was 0.000 which implies a significant difference between the studentsâ€™ writing skills taught using tutorial video and who were taught using conventional method, the experimental class taught using tutorial video produced better writing skills than using conventional method.